Analisis Kesulitan Menulis Teks Puisi Peserta Didik Kelas IV SDN 1 Dasan Baru Tahun Ajaran 2020/2021 - Jannah, Rofiqotul; Gunayasa, Ida Bagus Kade; Tahir, Muhammad (Pendagogia: Jurnal Pendidikan Dasar, 2022)
This study aims to determine the difficulties of students in writing poetry texts. This research is a content analysis research with a qualitative approach through three stages, namely data reduction, data presentation, and drawing conclusions. The subject of this research is a poetry document written by students of class IVB at SDN 1 Dasan Baru. The result of this research is the finding of students' difficulties in writing poetry texts. These difficulties include the difficulty of determining diction in the management of inappropriate words, the difficulty of typography in unattractive typographical arrangements, the difficulty of determining figurative language in the strength of expression, the difficulty of determining rhyme in determining the placement of sounds and their repetition, the difficulty of determining the tone in a poetic atmosphere want to convey.